The basic themes of talent management: Bibliometric analysis and systematic literature review - Roy Hendrawan; Reni Rosari; Tur Nastiti (Cogent Business & Management, 2024)
Over the past two decades, talent management research and literature has grown by 29.32% annually, with 1,415 articles and 2,903 authors. Despite its strategic importance, significant research gaps in talent management exist. This study identifies basic themes and gaps in talent management research through bibliometric analysis and a systematic literature review. We highlight that talent management practices, work engagement, social exchange theory, talent identification, and workforce differentiation are basic but underdeveloped themes. We present an integrated model outlining talent management's mechanisms, consequences, hypotheses, and managerial implications. Future research should incorporate social exchange theory with alternative theories like organizational justice, social identity, and person-environment fit. Empirical research should also examine mediators such as organizational justice, talent perception congruence, proactive behaviors, and moderators like generational differences, psychological contracts, and perceived procedural and interactional justice. Investigating positive and negative attitudinal and behavioral outcomes, focusing on impacts on both talents and non-talents, is crucial. Further exploration of contextualized talent management, especially in response to digital transformation, demographic shifts, and emerging economies, is necessary. Practical implications suggest integrating individual talent management practices to create a synergistic effect. This study enhances the understanding of talent management, providing valuable insights and references for researchers, scholars, and professionals.
Keywords: 650; Talent management practices; social exchange theory; work engagement; talent identification; high potential; workforce differentiation